On the concept of reason in P. Tillich’s "Systematic Theology" - Emelianenko, Anna (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2016)
The article deals with the epistemological foundations of P. Tillich’s theology. In particular, the article analyzes the concepts of subjective and objective, technical and ontological reason, the “depth” of knowledge in every possible way, historical and theological connotations of philosophical and epistemological theory.